Exploiting outage performance in device-to-device for user grouping - Dinh-Thuan Do; Chi-Bao Le (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The spectrum efficiency and massive connections are joint designed in new form of device-to-device for user grouping. A pair of users is implemented with nonorthogonal multiple access (NOMA) systems. Although NOMA benefits to such system in term of the serving users, device to device (D2D) faces the interference from normal cellular users (CUE). In particular, we derive exact formulas of outage probability to show system performance. In this article, we compare two schemes to find relevant scheme to implement in practice. The frame structure is designed with two timeslot related to uplink and downlink between the base station and D2D users. We confirm the better scheme in numerical result by considering the impacts of many parameters on outage performance.